GAMBAR BERCERITA RAMAH BERKATA Representasi Keteladanan dalam Gambar Bercerita di Dongeng Anak Corona Series - Ari Susanti (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
Fairy tale is one of the communication media to convey messages through stories so that they are easily understood by children. This research discusses the Dongeng Corona Series 2 by "Clean and Healthy Lifestyle Habits" which the duration of this video is 7 minutes 25 seconds can be accessed at YouTube channel in https://www.youtube.com/watch?v=kuxhgFw8648.  This study aims to discuss the meaning of exemplary and messages contained in the Dongeng Corona Series 2, where this fairy tale was created as a form of concern for the Central Java Human Initiative and Kak Kempho's Picture Story Studio in fighting Covid 19 by providing education to children through fairy tales. This research method uses semiotic analysis for picture messages and in-depth interviews with Kak Kempho to explore further data through zoom meetings. The research findings show that the role of the storyteller as a communicator as a determining factor for messages conveyed in fairy tales will be well received by communican. Some of these defining conditions are that the storyteller knowledge and the storyteller has a way to tell about a theme more easily for both children and parents to understand. Fairy tales also help people to explain those that are difficult to explain. The hope is that fairy tales can help people carry out a mental revolution from an early age.